2005
DOI: 10.1177/000331970505600413
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association Between Carotid Intima-Media Thickness and PAF-Acetylhydrolase Mass and Activity in Patients with Primary Hyperlipidemia

Abstract: Carotid intima media thickness (IMT), represents an important clinical indicator of early atherosclerosis. Human plasma platelet-activating factor acetylhydrolase (PAF-AH) is an enzyme primarily associated with low-density lipoprotein (LDL) while a small proportion of enzymatic activity is also associated with high-density lipoprotein (HDL). Plasma paraoxonase 1 (PON1) is an esterase exclusively associated with HDL. The authors investigated the possible relationship between carotid IMT and the plasma levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 40 publications
2
21
0
3
Order By: Relevance
“…Although it seems clear that PON1 activity status is a better predictor of coronary heart disease risk than any of the known PON1 genotypes [32], only a few studies investigated the effect of PON1 activity on IMT [20, 31, 33, 34]. Most of them failed to show a significant decrease in PON1 activity in CAAD [31, 33, 34]. However, we found a significant negative correlation between PON1 activity and IMT, as well as salt-stimulated PON1 activity and IMT in the whole study population.…”
Section: Discussionmentioning
confidence: 99%
“…Although it seems clear that PON1 activity status is a better predictor of coronary heart disease risk than any of the known PON1 genotypes [32], only a few studies investigated the effect of PON1 activity on IMT [20, 31, 33, 34]. Most of them failed to show a significant decrease in PON1 activity in CAAD [31, 33, 34]. However, we found a significant negative correlation between PON1 activity and IMT, as well as salt-stimulated PON1 activity and IMT in the whole study population.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the relationship between Lp-PLA 2 and carotid intima-media thickness (IMT), a marker of atherosclerotic disease, is not independent of other cardiovascular risk factors [26,39,50,51], whilst in the Mamlo Diet and Cancer Study, there was a weak association. Lp-PLA 2 activity and mass were associated with increased carotid IMT in an age-adjusted model but the model did not adjust for other traditional cardiovascular risk factors.…”
Section: Subclinical Atherosclerosismentioning
confidence: 99%
“…В частности, Kiortsis DH, et al [8] не выявили различий в активности ЛП-ФЛА2 в подгруппах с ТКИМ <0,7 мм и >0,7 мм среди пациентов с гиперлипидемией. Campo S, et al [7] не получили достоверных различий в уровне ЛП-ФЛА2, а также частоте полиморфных вариантов гена ЛП-ФЛА2 у больных с/без атеросклероза сонных артерий.…”
Section: Discussionunclassified
“…Недавно были опубликованы результаты мета-анализа 32 проспективных клинических исследований, согласно результатам которых уровни ЛП-ФЛА2 значимо связаны с риском ССЗ по типу непрерывной линейно-логарифмической зависимости [6]. В то же время не всем авторам удается выявить ассо-циацию уровней ЛП-ФЛА2 с развитием атеросклероза каротидных артерий [7,8], что может свидетельствовать о наличии расовых различий в реализации данной связи.…”
unclassified